Implications of the Cambridge Curriculum for the Development of Analytical Thinking Skills among Seventh-Grade International Class Programme Students in Social Studies Learning - Alfina Rosyidah; Siti Zazak Soraya (IAIN Madura, 2026)
21st-century education demands highly analytical thinking skills from students, particularly in Social Sciences (IPS) learning, to enable them to logically understand the dynamics of various social problems. However, pre-research data indicates that the analytical thinking skills of seventh-grade International Class Programme (ICP) students at MTsN 2 Ponorogo are still not optimal in learning. This qualitative case study aims to describe the implementation of the Cambridge Curriculum and analyze its real-world implications for the development of these students' analytical thinking skills. Field data collection was conducted through observation techniques, in-depth interviews, and structured documentation. Interactive data analysis included data condensation, data presentation, and comprehensive conclusion drawing. The results showed that the curriculum implementation was carried out through framework planning, student-centered learning with English as the medium of instruction, and formative and summative evaluations. The implications of implementing this curriculum were proven to improve students' cognitive abilities in identifying important information, distinguishing facts from opinions, strengthening logical argumentation structures, and connecting concepts with real phenomena. In conclusion, the curriculum is highly effective.